An HTTP/RDF-Based Agent Infrastructure for Manufacturing Using Stigmergy - Schraudner, Daniel; Charpenay, Victor (The Semantic Web: ESWC 2020 Satellite Events, 2020)
We have built a demonstrator for the communication infrastructure of a multi-agent system controlling a simplified shop floor. We use the concept of stigmergy which does not allow inter-agent communication but only between agents and the environment. Furthermore we keep the agents as simple as possible by using only simple-reflex agents. The environment is modelled as a RDF Knowledge Graph and communication takes place using HTTP request. We carried out experiments regarding the agent scalability and identified open questions.<br
Keywords: Multi-agent system; Stigmergy; Knowledge graph